A standardized definition for right ventricular failure in cardiac surgery patients. (9th March 2022) - Jabagi, Habib; Nantsios, Alex; Ruel, Marc; Mielniczuk, Lisa M.; Denault, André Y.; Sun, Louise Y.
Abstract: Right ventricular failure (RVF) is a significant cause of mortality and morbidity after cardiac surgery. Despite its prognostic importance, RVF remains under investigated and without a universally accepted definition in the perioperative setting. We foresee that the provision of a standardized perioperative definition for RVF based on practical and objective criteria will help to improve quality of care through early detection and facilitate the generalization of RVF research to advance this field. This article provides an overview of RVF aetiology, pathophysiology, current diagnostic modalities, as well as a summary of existing RVF definitions. This is followed by our proposal for a standardized definition of perioperative RVF, one that captures RV structural and functional abnormalities through a multimodal approach based on anatomical, echocardiographic, and haemodynamic criteria that are readily available in the perioperative setting (Central Image).